Strategi Pembinaan Sepak Bola Usia 23 TahunDi Klub Citra Bakti Ngada - Rewo, Josep Marsianus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to improve the skills of coaches and 23-year-old soccer players at the Citra Bakti Ngada Club in implementing effective, systematic, and scientifically based coaching strategies. Based on initial observations, coaches and players still face challenges in training planning, time management, and the implementation of modern game strategies. The research methods used included outreach, training, field practice mentoring, and evaluation. The results indicate an increase in coaches' understanding of the principles of periodized training, variations in technical and tactical training methods, and improvements in players' physical performance and discipline. Therefore, this study makes a significant contribution to improving the quality of soccer coaching for 23-year-olds at the regional level. Keywords: Soccer Coaching, Training Strategy, 23-Year-Olds, Community Service, Citra Bakti Ngada.